False gingival enlargement as a diagnostic problem: a case report - L Kesic (Journal compilation 2008 Blackwell Munksgaard)
The aim of the case report was to describe gingival enlargement in a patient who came to the Department of Oral Medicine and Periodontology at NisË‡ Dental Clinic.